Growth of PbS nanopyramidal particulate films for potential applications in quantum-dot photovoltaics and nanoantennas - Hawaldar, Ranjit R.; Mulik, Uttam P.; Patil, K.; Pasricha, R.; Sathaye, S.; Lewis, A.; Amalnerkar, Dinesh P. (Materials Research Bulletin, 2005)
We report a simple interfacial process called the liquid-liquid interface reaction technique (LLIRT) that leads to the formation of nanosized PbS particulate films with hitherto unreported pyramidal morphology. The resultant PbS films were characterized by transmission electron microscopy (TEM) with selected area electron diffraction (SAED), X-ray diffractometery (XRD), atomic force microscopy (AFM), near field scanning optical microscopy (NSOM) and UV-vis spectroscopy. The pyramidal morphology is speculated to originate from the preferred orientation of the 2 2 0 plane of cubic PbS. Our nanopyramidal PbS particulate films display remarkably sharp excitonic peak centered around 656 nm that accounts for a band gap of 1.8 eV suggesting, in turn, their potential application in QD photovoltaics. Interestingly, the feasibility of such nanopyramids to potentially act as nanoantennas (as revealed by the NSOM) is also suggested. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Atomic force microscopy; Chemical synthesis; Electron microscopy; Nanostructures; Optical properties

Novel polymer-inorganic solid-state reaction for the synthesis of CdS nanocrystallites - Kanade, K. G.; Hawaldar, Ranjit R.; Pasricha, R.; Radhakrishnan, S.; Seth, T.; Mulik, Uttam P.; Kale, B. B.; Amalnerkar, Dinesh P. (Materials Letters, 2005)
We offer a novel polymer-inorganic solid-state reaction route for the in situ generation of nanochalcogenide semiconductor in the network of polymer which itself acts as a chalcogen source. We have exemplified feasibility of this route by reacting CdI2 with engineering thermoplastic polyphenylene sulphide (PPS). These two reactants in 1:1 and 10:1 molar ratios were simply heated at the crystalline melting temperature of PPS. The resultant products were characterized by X-ray diffractometry, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM, with selected area electron diffraction). The prima facie observations revealed the formation of cubic nanocrystallites of US with the particle size ranging from 6 to 20 nm entrapped in modified (cyclized) PPS matrix when the reactants were taken in 10:1 molar ratio. A tentative mechanism has been suggested for such hitherto unattempted solid-state reaction. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: CdS nanocrystallites; Semiconductor; solid-state reaction; Thermoplastic polymer matrix

Self-assembly of nanostructured PbS for solar photovoltaic applications - Hawaldar, Ranjit R.; Kanade, K. G.; Patil, K. R.; Sathaye, S. D.; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Materials Chemistry and Physics, 2005)
In the present communication, the self-assembly of nanocrystalline PbS at the liquid-liquid interface is reported. The PbS nanocrystals were, subsequently, transformed in the form of thin films by dip coating. The resultant Q-PbS films were characterized by SEM-EDAX, TEM-SAED, XRD, XPS and UV-vis Spectroscopy. Pyramidal features at the nanometer scale, preferred orientation along (2 2 0) and (4 0 0) planes of cubic structure and a sharp excitonic peak at 656 run are the salient aspects of this work. The band-gap of the order of 1.8 eV (associated with the excitonic feature) is ideally suited for solar photovoltaic applications. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Liquid-liquid interface; nanopyramid; Nanostructures; PbS

Studies on gas sensing performance of pure and modified barium strontium titanate thick film resistors - Jain, G. H.; Patil, L. A.; Patil, P. P.; Mulik, Uttam P.; Patil, K. R. (Bulletin of Materials Science, 2007)
Barium strontium titanate ((Ba0.87Sr0.13)TiO3-BST) ceramic powder was prepared by mechanochemical process. The thick films of different thicknesses of BST were prepared by screen-printing technique and gas-sensing performance of these films was tested for various gases. The films showed highest response and selectivity to ammonia gas. The effect of film thickness on gas response was also studied. As prepared BST thick films were surface modified by dipping them into an aqueous solution of titanium chloride (TiCl3) for different intervals of time. Surface modification shifted response to H2S gas suppressing the responses to ammonia and other gases. The surface modification, using dipping process, altered the adsorbate-adsorbent interactions, which gave the unusual sensitivity and selectivity effect. Sensitivity, selectivity, thermal stability, response and recovery time of the sensor were measured and presented.
Keywords: (Ba0.87Sr0.13)TiO3 thick films; ammonia gas sensor; II2S gas sensor; selectivity; sensitivity

XPS and AFM investigations on silver-based photoimageable thick film systems - Umarji, Govind; Ketkar, Supriya; Hawaldar, Ranjit R.; Gosavi, Suresh W.; Patil, Kashinath; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Microelectronics International, 2008)
Purpose - The purpose of this paper is to ascertain chemical changes occurring at various stages involved in processing of silver-based photoimageable thick films; and to determine ensuing topographical features which other wise appeared to be hindered in 2D scanning electron microscopy. Design/methodology/approach - Surface sensitive techniques, viz. X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM) were used. Findings - Interfacial adhesion of silver film with substrate (Al(2)O(3)) was specifically looked into with respect to role played by photoimaging (before and after exposure to ultra-violet light). XPS results revealed occurrence of subtle chemical changes in terms of unsaturation to saturation in C-C bonding and also an interesting C-Al bonding which presumably improves mechanical adhesion of unfired film with the alumina substrate. AFM was carried out to examine the surface roughness, particle size, and microstructure of film which are very important from the standpoint of high-frequency applications. Originality/value - Surface sensitive techniques like XPS and AFM were exclusively used in order to characterize silver-based photoimageable thick films.
Keywords: microscopy; Silver; thick film circuits; X-rays

Concurrent In-situ formation of Ag/Ag2S nanoparticles in polymer matrix by facile polymer-inorganic solid state reaction - Waghmare, Sujata; Shinde, Manish; Gholap, Ramkrishna S.; Rao, N. Koteswara; Hawaldar, Ranjit R.; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Journal of Nano Research, 2009)
We herein report the feasibility of polymer-inorganic solid-state reaction route for simultaneous in situ generation of Ag & Ag2S nanostructures in polymer network wherein an engineering thermoplastic, polyphenylene sulphide (PPS), itself acts as a chalcogen source as well as a stabilizing matrix for the resultant nanoproducts. Typical solid-state reaction was accomplished by simply heating the physical admixture of the two reactants i.e. AgNO3 and PPS by varying molar ratios mainly 1:1, 1:5, 1:15, 1:20, at the crystalline melting temperature (285 degrees C) of PPS. The synthesized nanoparticles were characterized by various physico-chemical techniques like X-ray Diffractometry, Scanning Electron Microscopy equipped with EDAX, Transmission Electron Microscopy and UV-Visible spectroscopy. The prima facie observations suggest the effective formation and subsequent entrapment of mainly nanocrystalline metallic silver (fcc) in PPS matrix for all the molar ratios chosen for the reaction. Additionally, simultaneous occurrence of nanocrystalline Ag2S (monoclinic phase) is also noticed in case of heated admixture of AgNO3: PPS with equimolar ratio. The TEM analysis reveals nanoscale polydispersity (5nm to 70nm) and prevalence of mainly spherical morphological features in all the cases with occasional indications of triangular and hexagonal morphological features depending upon the reaction molar ratio.
Keywords: Ag; Ag2S; Nanoparticles; Polymer inorganic solid -state reaction; Thermoplastic polymer matrix

Fabrication, thermal and electrical properties of polyphenylene sulphide/copper composites - Goyal, R. K.; Kambale, K. R.; Nene, S. S.; Selukar, B. S.; Arbuj, Sudhir S.; Mulik, Uttam P. (Materials Chemistry and Physics, 2011)
The thermal and electrical properties of high performance poly(phenylene sulphide) (PPS) composites reinforced up to 31 vol% Cu particles were investigated to be used as materials for electronic applications. The thermal stability and char yield of the composites increased significantly. Both pre- and post- glass transition coefficient of thermal expansion (CTE) of composites decreased significantly. The microhardness was increased by more than 50% compared to pure PPS matrix. Microhardness and CTE of composites correlated well with the rule of mixtures. A percolation threshold about 6 vol% Cu was obtained. The electrical conductivity was increased by about eight orders of magnitude for 18 vol% composite. Dielectric constant and dissipation factor of composites at 1 MHz was increased by about 6-fold and 70-fold compared to matrix, respectively. They decreased gradually with increasing frequency up to 1 MHz and thereafter, there was insignificant change. The scanning electron microscope showed almost uniform distribution of Cu particles in the matrix. Owing to better dimensional stability and good electrical properties, these composites are very promising for electronic applications. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Dielectric property; Electrical conductivity; hardness; Thermal expansion

Hierarchical CdS nanostructure by Lawesson's reagent and its enhanced photocatalytic hydrogen production - Pandit, Vikram U.; Arbuj, Sudhir S.; Hawaldar, Ranjit R.; Kshirsagar, Pradnya V.; Deshmukh, Amarsinh J.; Ambekar, Jalindar D.; Mulik, Uttam P.; Gosavi, Suresh W.; Kale, Bharat B. (RSC Advances, 2015)
Lawesson's reagent (LR) has been effectively exploited for the synthesis of hierarchical architectures of cadmium sulphide (CdS) nanostructures for the first time. The X-ray diffractograms of the as synthesised CdS nanostructures confirm the formation of hexagonal CdS. The broadness of the XRD peaks clearly indicates the nanocrystalline nature of CdS with average crystallite size of 4 nm. A FESEM study revealed the formation of hierarchical nanostructures, whereas a TEM study showed that the hierarchical arrangement is composed of nanosized CdS particles. A band-gap i.e. 2.4 eV was derived from diffuse reflectance spectroscopy. The photoluminescence spectrum showed an emission peak at 535 and 568 nm which can be attributed to band-edge emission and surface emissions or possible metal vacancies, respectively. Considering the band-gap within the visible region, the photocatalytic hydrogen evolution performance of these CdS nanostructures was performed under visible light irradiation from hydrogen sulphide and water, respectively. Utmost hydrogen evolution i.e. 14 136 mu mol h(-1) g(-1) and 2065 mu mol h(-1) g(-1) was observed over a naked CdS nanostructure via H2S and water decomposition, respectively. The amount of hydrogen obtained by H2S splitting is much higher as compared to earlier reports.

Tuning magnetic behavior of nanoscale cobalt sulfide and its nanocomposite with an engineering thermoplastic - Rumale, Narendra; Arbuj, Sudhir S.; Umarji, Govind; Shinde, Manish; Mulik, Uttam P.; Joy, Pattayil Alias; Amalnerkar, Dinesh P. (Journal of Electronic Materials, 2015)
Nanocomposites containing magnetic nanoparticles embedded in a polymer matrix with good thermal stability (up to 200A degrees C) are technologically important. We report an environmentally benign solid-solid approach for synthesis of cobalt sulfide and its nanocomposite using a thermally stable matrix of polyphenylene sulfide. Physicochemical characterizations reveal the formation of nanoclusters of the hexagonal phase CoS. Even though bulk CoS is nonmagnetic, magnetization studies exhibit anomalous magnetic behavior for phase-pure nanoscale CoS and its nanocomposites.
Keywords: Nanocomposite; polyphenylene sulfide; Solid-solid reaction; superparamagnetic